Industry 4.0 and the circular economy: Integration opportunities generated by startups - Tiago H. H. Silva; Simone Sehnem (Logistics, 2022)
Background: The purpose of this study is to analyze the adoption and implementation of technologies related to Industry 4.0 and the integration with circular economy (CE) to minimize the effects of resource scarcity in emergency situations. Method: The study was developed in two stages: The first consists of a systematic review of the literature for analytical categorization of the technologies of Industry 4.0 that can be useful for implementation in the circular economy. In the second step, empirical validation was carried out with 45 foodtech startups from the agribusiness value chain, farm to table, reuse, and waste management and disposal segments. Results: The contributions of the study show that: (i) The business models of startups in the food segment are closely aligned with the assumptions of circular economy. (ii) The technologies of industry 4.0 are supporting the implementation of circular economy in foodtech companies. (iii) Digitization, traceability, software as a service, traceability, digital solutions, and shared platforms occupy the leadership in the interface between CE and industry 4.0. (iv) Partnerships are strategic elements in the creation of innovative ecosystems for the success of foodtech startups. Conclusions: We conclude this paper with a diagnosis about companies involved in the foodtech segment in addition to the proposition of a business and sectorial agenda to consolidate the Industry 4.0 technologies in order to promote circular economy.
Keywords: 650; sustainability; circular supply; circularity of resources; smart assets; startups